Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4269/ajtmh.15-0004
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Diagnosis Across the International Centers of Excellence for Malaria Research: Platforms, Performance, and Standardization

Abstract: Diagnosis is “the act of identifying a disease, illness, or problem by examining someone or something.” When an individual with acute fever presents for clinical attention, accurate diagnosis leading to specific, prompt treatment often saves lives. As applied to malaria, not only individual patient diagnosis is important but also assessing population-level malaria prevalence using appropriate diagnostic methods is essential for public health purposes. Similarly, identifying (diagnosing) fake antimalarial medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 91 publications
(85 reference statements)
0
29
0
Order By: Relevance
“…Published data from Peru indicate that P. falciparum field isolates commonly lack the pfhrp2 gene (the main target used by previously used RDTs) limiting further the use of some RDTs 66. Another study with RDTs in this region, also showed cross-reactions of P. vivax samples with the Pf-pLDH or PfHRP2 tests; P. falciparum -positive samples with high parasitemias cross-reacted with Pv-pLDH 23. Based on these observations, the ideal RDT to be used in remote areas of the Peruvian Amazon should target Pf-pLDH and Pv-pLDH separately in the same device, with good heat stability and better sensitivity.…”
Section: Detection Of P Vivax Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data from Peru indicate that P. falciparum field isolates commonly lack the pfhrp2 gene (the main target used by previously used RDTs) limiting further the use of some RDTs 66. Another study with RDTs in this region, also showed cross-reactions of P. vivax samples with the Pf-pLDH or PfHRP2 tests; P. falciparum -positive samples with high parasitemias cross-reacted with Pv-pLDH 23. Based on these observations, the ideal RDT to be used in remote areas of the Peruvian Amazon should target Pf-pLDH and Pv-pLDH separately in the same device, with good heat stability and better sensitivity.…”
Section: Detection Of P Vivax Infectionmentioning
confidence: 99%
“…Despite the increasing research conducted in Peru over the past decade on P. vivax malaria epidemiology,1721 diagnostics,22,23 treatment,12,13,24 vector biology,2528 and molecular genetics,2931 several knowledge gaps still need to be addressed to support the Peruvian NMCP, so that malaria transmission hotspots can be readily identified and that the NMCP can more effectively implement strategies that target such areas with effective interventions 32. In this review, the trends in P. vivax incidence are described in relation to major control efforts implemented in Peru over the past 70 years.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostics remain fundamental to molecular epidemiology. Although many specific aspects of malaria diagnostics are discussed separately in this supplement, 5 here we address those issues that relate to disease ecology and transmission dynamics.…”
Section: Assessing Malaria Prevalence and Transmissionmentioning
confidence: 99%
“…Although with good sensitivity in diagnosing malaria, its reliability relies upon good-quality slide preparation and well-trained staff in parasite detection and differentiation, especially at low parasite densities [ 2 ]. In many peripheral health centres of endemic countries, microscopy is not available [ 3 ] due to limited resources or lack of expertise [ 4 ]. Simpler and rapid methods of identification of parasites may be useful for prompt diagnosis and appropriate treatment especially in peripheral health posts where microscopy is not available [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria rapid diagnostic tests (RDTs), based on immunochromatographic parasite antigen detection, are of great value in endemic regions. Since 2010, WHO has recommended either RDT or microscopy confirmation of suspected malaria cases before treatment [ 3 ]. However, it remains unclear whether RDTs are useful in field conditions in low transmission areas [ 6 ] since their reliability is limited by the lack of detection of low-density parasitaemia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%